Влияние кремнезема на спектральные и фотофизические свойства родамина 6Ж в полиуретановой матрице - Безродна, Т.В.; Антоненко, О.И.; Косянчук, Л.Ф.; Рощин, А.Н.; Безродный, В.И.; Негрийко, А.М.; Ясковец, А.О. (Доповіді НАН України, 2019)
Создан органо-неорганический нанокомпозит на основе окрашенного ксантеновым красителем родамин 6Ж
и допированного диоксидом кремния полиуретанакрилата. Исследованы спектральные и фотофизические
свойства. Показано, что внедрение наночастиц аэросила в полимерную матрицу увеличивает фотостойкость красителя и интенсивность люминесценции. Створено органо-неорганічний нанокомпозит на основі забарвленого ксантеновим барвником родамін 6Ж
і допованого діоксидом кремнію поліуретанакрилату. Досліджено спектральні та фотофізичні властивості.
Показано, що введення наночастинок аеросилу у полімерну матрицю збільшує фотостійкість барвника та
інтенсивність люмінесценції. The organo-inorganic nanocomposite based on rhodamine 6G with xanthene dye and polyurethane acrylate
doped with silicon dioxide has been developed. Spectral and photophysical properties of the dye in the polymer
matrix have been investigated in the dependence on the concentration of SiO₂ nanoparticles (1, 2, 4, and
8 mass. %). Aerosil concentration growth results in an increase of the R6G monomer–dimer ratio, which is seen on
the absorption curves as an intensification of the spectral peak at 535 nm (a monomer state) relative to the spectral
component at 505 nm (an aggregated state of the H-type). Adding the SiO₂ nanoparticles to the polymer
matrix enhances the dye luminescence intensity almost twice for a SiO₂ concentration of 8 mass. %. This effect is
caused by a decrease of the dimer luminescence reabsorption, since the dimer amount is smaller in the orga noinorganic
nanocomposite, compared to the pure PUA. The photostability growth is observed for the R6G dye in
the PUA polymer matrix doped with aerosil nanoparticles. Application of the organo-inorganic materials
with the SiO₂ concentration in polyurethane acrylate up to 8 mass % is shown to be promising for the development
of efficient active elements for the dye lasers, pumped by the second harmonic of a neodymium laser.